An ethnobotanical study of medicinal plants used to treat skin diseases in northern Pakistan - Khafsa Malik; Mushtaq Ahmad; Muhammad Zafar; Riaz Ullah; Hafiz Majid Mahmood; Bushra Parveen; Neelam Rashid; Shazia Sultana; Syed Nasar Shah; Lubna (BMC, 2019)
Abstract Background Skin diseases are a major health concern especially in association with human immune deficiency syndrome and acquired an immune deficiency. The aim of this study was to document the ethnomedicinal information of plants used to treat skin diseases in Northern Pakistan. This is the first quantitative ethnobotanical study of therapeutic herbs utilized by the indigenous people of Northern Pakistan for skin diseases. Methods Interviews were taken to obtain information from 180 participants. Quantitative methods including fidelity level (FL), Frequency of citation (FC), Use-value (UV), Jaccard indices (JI), Family importance value (FIV), Relative frequency of citation (RFC) and Chi-square test were applied. Medicinal plants uses are also compared with 50 national and international publications. Results In this study, we recorded 106 plant species belonged to 56 floral families for treatment of skin ailments. The dominant life form reported was herb while the preferred method of utilization was powder, along with leaf as the most used plant part. RFC ranges from 0.07 to 0.25% whereas the highest FIV was recorded for family Pteridaceae. FL values range from 36.8 to 100%. The study reported 88% of new plant reports for the treatment of skin diseases. Conclusion The present study revealed the importance of several plants used to treat skin diseases by the local communities of Northern Pakistan. The available literature supported the evidence of plant dermatological properties. Plants having high UV and RFC can be considered for further scientific analysis. There is dire need to create awareness among local, government and scientific communities for the preservation of medicinal species and ethnomedicinal knowledge in Northern Pakistan.